PENERAPAN KOMPRES DINGIN DALAM MANAJEMEN NYERI PADA PASIEN CLOSE FRAKTUR FEMUR DI RUANG RSUP Dr. TADJUDDINCHALID MAKASSAR - Nurul Hijriyah; Yusrah Taqiyah; Wan Sulastri Emin; Muhajiri Maliga (CV. Adiba Aisha Amira, 2026)
Background: Fractures are a health problem that often cause severe pain, limited activity, and the risk of complications. Pain management usually involves pharmacological therapy, but long-term use can lead to dependence and side effects. As an alternative, non-pharmacological therapies such as cold compresses are effective in relieving pain through vasoconstriction, which reduces blood flow, inflammation, and oedema in the injured area. Objective: To determine the application of cold compresses in pain management and to evaluate their effectiveness in reducing pain intensity in patients in the Emergency Room of Dr. Tadjuddin Chalid General Hospital. Method: The method used included assessment, nursing diagnosis, intervention planning, implementation, and evaluation. Results: The assessment showed that patients experienced acute pain with a pain scale of 6–7/10. After applying cold compresses for 15–20 minutes every 8 hours, there was a decrease in pain intensity to a scale of 2–3/10. The evaluation showed that the patient was more relaxed, appeared cooperative, and reported a significant reduction in pain. Conclusion: From this case study, the application of cold compresses was proven to be effective as a non-pharmacological measure in reducing pain intensity in patients with femur fractures. This intervention can be used as an additional option in nursing care to increase comfort, reduce drug dependence, and support the holistic healing process of patients.